Effect of micronutrient deficiency on protozoal infection in stunting toddler - Utami, Wiwien Sugih; Ramadanti, Novi Awalia; Rachmawati, Dwita Aryadina; Ratnawati, Leersia Yusi; Armiyanti, Yunita; Hermansyah, Bagus (Alma Ata University Press, 2024)
Background: Stunting is a developmental disorder caused by chronic inadequate nutritional intake in toddlers, leading to deficiencies in various nutrients, including iron and zinc. This can weaken toddlers' immunity, making them more vulnerable to infectious diseases, such as intestinal protozoa. An infected digestive tract can interfere with absorbing nutrients and reduce appetite, causing the infection to persist and become chronic. Chronic infection triggers the formation of pro-inflammatory cytokines that affect bone growth, hindering growth and causing stunting.Objectives: This study confidently investigates the correlation between iron and zinc micronutrient intake and intestinal protozoan infection in stunting toddlers in Jember District.Methods: The research is observational and cross-sectional, with 568 stunting toddlers aged 0-59 months in Jember District, East Java as study subjects. Iron and zinc intake were collected through 2x24-hour food-recall questionnaire interview and processed using the Nutrisurvey software. Protozoan infection status in toddler feces samples was identified using direct smear and modified Ziehl-Neelsen methods. The data analysis method chosen was the Spearman correlation test.Results: The study found that stunted toddlers in Jember District had mostly deficient micronutrient intake. The average iron intake is 2.56±3.06 mg and the average zinc intake is 1.8±1.47 mg. Protozoan infection was found in this study has a prevalence of 15.7%, with identified species including Entamoeba histolytica (3.3%), Giardia lamblia (2.6%), Cryptosporidium parvum (3.2%), Blastocystis hominis (5.3%), and mixed infections (1.2%). The statistical analysis confirms that there is no significant correlation between the intake of micronutrients iron (p=0.91;r=0.005) and zinc (p=0.76;r=0.013) and intestinal protozoan infection in stunting toddlers in Jember District.Conclusions: Based on the data, protozoan infection may be caused by multiple factors, such as parenting practices and family socioeconomics. However, improving nutrition by education and giving additional supplementation are crucial to reduce the prevalence of malnutrition in toddlers.